Perceptual Inhibition Is Not a Specific Component of the Sensory Integration Process Necessary for a Rapid Voluntary Step Initiation in Healthy Older Adults. (10th May 2019) - Magnard, Justine; Berrut, Gilles; Couturier, Catherine; Cattagni, Thomas; Cornu, Christophe; Deschamps, Thibault
Abstract: Objectives: We investigated whether performing step initiation during a proprioceptive perturbation would require greater perceptual or motor inhibitory control in older adults. Method: Fifty-two healthy adults (young: n = 26, mean age 22.5 years vs. older: n = 26, mean age 70.1 years) performed a stepping reaction time task, with different inhibition requirements (i.e., perceptual vs. motor inhibitory conflict), with two proprioceptive configurations: with and without application of Achilles tendon vibrations. Results: Beyond a systematically greater stepping reaction time in older adults ( p < .01), no difference was found between the perceptual versus motor inhibitory conflict resolution, regardless of age and proprioceptive configuration. Furthermore, slower reaction time was observed for young participants in the presence of Achilles tendon vibrations unlike older adults, who showed the same reactive stepping performance with or without vibrations ( p < .05). Discussion: These findings show that perceptual inhibition cannot be considered as specifically involved in the central processing of proprioceptive signals, at least not in active older adults. Rather than motor system malfunctioning or a reduced amount of proprioceptive afference, we propose that cortical-proprioceptive processing in older adults remains as effective as in young adults, regardless of the high attentional requirements for step responses.